(untitled) (Orinoquia, 2013)
This investigation was aimed at estimating digestible lysine level for maximum animal husbandry performance and the best characteristics regarding pigs in their grow-finishing phase fed on rice sub-product-containing rations. Forty 67.63 ± 2.53 kg Landrace x Large White x Pietrain crossbred pigs were used in a randomised complete block experimental design involving four treatments, five repeats and two animals per experimental unit. The treatments consisted of a base isoproteicisocaloricration having four L-lysine supplementation levels (0.000, 0.191, 0.382 and 0.584), resulting in rations containing0.53, 0.68, 0.83 and 0.98% digestible lysine. Lysine level had no effect on ration (energy)consumption; however, it had a quadratic effect (p<0.05)on weight-gain(0.771, 0.901, 0.848 and 0.844 kg, respectively), loineye area(34.31, 39.83, 43.61 and 39.19 cm2respectively),pork leg weight (8.92, 10.07, 10.07 and 9.78 kg respectively),linear form (p<0.05),daily lysine consumption (12.2; 16.3; 18.6 and 20.7 g respectively) and feed conversion(3.04; 2.75; 2.65 and 2.50 respectively). Digestible lysine level ensuring the greatest weight gain was estimated at 0.795% for pigs in the 67-85 kg live weight range, fed on diets containing rice subproducts. Key words: alternative feed; yield; nutritional requirement; pig-farming.